2022
DOI: 10.1186/s12943-021-01485-6
|View full text |Cite
|
Sign up to set email alerts
|

EWSR1-induced circNEIL3 promotes glioma progression and exosome-mediated macrophage immunosuppressive polarization via stabilizing IGF2BP3

Abstract: Background Gliomas are the most common malignant primary brain tumours with a highly immunosuppressive tumour microenvironment (TME) and poor prognosis. Circular RNAs (circRNA), a newly found type of endogenous noncoding RNA, characterized by high stability, abundance, conservation, have been shown to play an important role in the pathophysiological processes and TME remodelling of various tumours. Methods CircRNA sequencing analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 66 publications
3
140
1
Order By: Relevance
“…Immune escape, a key link in tumor proliferation, may be achieved by exosomal cargo-mediated m 6 A methylation. For instance, circNEIL3 contained in exosomes secreted by glioma cells accelerates tumor evasion of immune surveillance by blocking HECTD4-mediated ubiquitination to stabilize the m 6 A methylation regulator, IGF2BP3, and promote an immunosuppressive phenotype in macrophages [ 184 ]. Interestingly, tumor proliferation requires oxygen consumption and hypoxia promotes release of exosomes from tumor cells [ 174 ], Tu-Exo supports PMN formation by metabolic reprogramming or directly affecting immune cell function, facilitating tumor metastasis and invasion.…”
Section: A Methylation Remodels Immunosuppressive Tme By Directly Aff...mentioning
confidence: 99%
“…Immune escape, a key link in tumor proliferation, may be achieved by exosomal cargo-mediated m 6 A methylation. For instance, circNEIL3 contained in exosomes secreted by glioma cells accelerates tumor evasion of immune surveillance by blocking HECTD4-mediated ubiquitination to stabilize the m 6 A methylation regulator, IGF2BP3, and promote an immunosuppressive phenotype in macrophages [ 184 ]. Interestingly, tumor proliferation requires oxygen consumption and hypoxia promotes release of exosomes from tumor cells [ 174 ], Tu-Exo supports PMN formation by metabolic reprogramming or directly affecting immune cell function, facilitating tumor metastasis and invasion.…”
Section: A Methylation Remodels Immunosuppressive Tme By Directly Aff...mentioning
confidence: 99%
“…Interestingly, the RBPs and their substrate RNAs are detected in EVs, and EVs can harbour sequence motifs to mirror the activity of RBPs 118 . circNEIL3 is packaged into exosomes and then transmitted to tumor associated macrophages (TAMs) that enable them to acquire immunosuppressive effect by stabilizing IGF2BP3, and promoting glioma progression 119 . EVs secreted by melanoma cells regulate the effect of IGF2BP1 on metastasis, and in turn, IGF2BP1 affects the cargo of the EVs 120 .…”
Section: The Oncogenic Role Of Igf2bps In Cancermentioning
confidence: 99%
“…Both Villarroya Beltri and Gao et al. have found that hnRNPA2B1 could recognize the GGAG motif in the 3’ sides of miRNA and result in specific miRNAs to be packed into exosomes ( 97 , 98 ). Similarly, Koppers-Lalic et al.…”
Section: Effects Of Adipose Tissue-derived Exosomal Cargo On Metaboli...mentioning
confidence: 99%